2021
DOI: 10.3389/fpos.2021.661257
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frames on COVID-19 Vaccine Resistance

Abstract: In order to control the spread of infectious diseases such as COVID-19, it will be important to develop a communication strategy to counteract “vaccine resistance”, that is, the refusal to take the COVID-19 vaccine even when available. This paper reports the results of a survey experiment testing the impacts of several types of message content: the safety and efficacy of the vaccine itself, the likelihood that others will take the vaccine, and the possible role of politics in driving resistance to the vaccine.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 67 publications
6
76
0
Order By: Relevance
“…Political conflict and coverage surrounding the nature and risk of the virus set the stage for segments of the public to be relatively more receptive to misinformation about COVID-19 vaccines. 34 Attitudes toward receiving a vaccine can be “understood as a continuum ranging from outright refusal to active demand for immediate uptake.” 35 (p1), 36 , 37 Since the beginning stages of testing for COVID-19 vaccines, polls indicated that a sizeable percentage of people in the United States were vaccine resistant , defined as unwilling to get vaccinated once one became available. 38 Many people were also vaccine hesitant , defined as a preference to wait for others have been vaccinated before deciding for themselves.…”
Section: Politicization Of the Covid-19 Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…Political conflict and coverage surrounding the nature and risk of the virus set the stage for segments of the public to be relatively more receptive to misinformation about COVID-19 vaccines. 34 Attitudes toward receiving a vaccine can be “understood as a continuum ranging from outright refusal to active demand for immediate uptake.” 35 (p1), 36 , 37 Since the beginning stages of testing for COVID-19 vaccines, polls indicated that a sizeable percentage of people in the United States were vaccine resistant , defined as unwilling to get vaccinated once one became available. 38 Many people were also vaccine hesitant , defined as a preference to wait for others have been vaccinated before deciding for themselves.…”
Section: Politicization Of the Covid-19 Vaccinementioning
confidence: 99%
“…In addition, messages that suggested the vaccine was being rushed for approval prior to the Presidential election decreased reported intentions to get vaccinated. 35 …”
Section: What Does Social Science Research Conclude About Promoting Vaccine Acceptancementioning
confidence: 99%
“…We are aware of but a few experimental studies addressing hesitancy to vaccinate against COVID-19. In Palm et al [17], a convenience sample of US-based Amazon MTurk workers was targeted in August 2020. Compared with the control group receiving no additional information, those who received a message about the safety and efficacy of the vaccine were more likely to say they would take it (and, of less practical importance, some manipulations decreased the willingness to be vaccinated).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many intervention studies have shown that describing positive behaviors as typical has the potential to introduce social change in a variety of domains (e.g., Behavioural Insights Team, 2012;Gerber & Rogers, 2009;Goldstein et al, 2008). Some studies have shown the same effect in the domain of vaccination: participants reported greater vaccination intentions when presented with a higher vaccination rate among their peers (Belle & Cantarelli, 2021;Hershey et al, 1994;Palm et al, 2021;Romley et al, 2016). This finding, however, was not corroborated in several other experiments (Clayton et al, 2021;Sinclair & Agerström, 2021;Xiao & Borah, 2020).…”
Section: Vaccination Rates As a Source Of Normative Influencementioning
confidence: 96%